Identification, antimicrobial resistance, and biofilm-forming capability of bacterial isolates from bovine mastitis in the high-altitude region of Shannan, Tibet - Yunxia Guo; Mingqiong Wang; Yihan Yin; Ling Shi; Wenxin Cao; Yanting Du; Junhao Zhang; Dawa Zhuoga; Ouzhu Cuomu; Shaowen Li; Jie Chen; Changmin Hu (Archives of Microbiology, 2026)

Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Speciation and light-absorbing properties of carbonaceous aerosols in a typical industrial city, Taiyuan, China - Ziyong Guo; Chenhui Li; Fengxian Liu; Ying Wei; Jiajie Li; Yanting Qiu; Taomou Zong; Ling Mu; Zhijun Wu; Jiancheng Wang (Atmospheric Environment, 2026)

The process of trace metals enrichment in pyrite under methane seepage in the northern South China Sea - Yanting Ling; Xuan Chen; Daidai Wu; Qinyi Zhang; Shengyi Mao; Guangrong Jin; Jie Liu; Haizhen Zhai; Chao Yang; Zheng Su; Nengyou Wu (Frontiers in Marine Science, 2025)
Pyrite is an important indicator of methane seepage. The effects of organic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) on the trace metals in pyrite have aroused interest; however, further studies about how these two pathways control the trace element patterns are still required. Therefore, we studied the geochemical and mineralogical characteristics of sediment samples from the northern South China Sea, aiming to investigate the enrichment mechanisms of trace elements into pyrites in methane seep systems. We applied laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) to analyze the trace element patterns of pyrites in core Z22–3. We used Sr/Ca-Mg/Ca, (Mo/U) EF values, chromium reducible sulfur (CRS) content, total organic carbon (TOC), δ 34 S, and δ 13 C values of bulk sediments to determine the position of sulfate–methane transition zones (SMTZs). Progressively more positive δ 34 S values (up to −36.54‰) of the CRS and an increase in Mg/Ca indicate the enhancement of SD-AOM, suggesting that the position of SMTZs is located at depths of 181 to 481 and 1,101 to 1,401 cmbsf. Within SMTZs, pyrites exhibit obvious enrichments in Co, Ni, Mo, and Pb and depletion in Mn, Zn, Cu, and V. We discuss the process of methane seepage affecting trace elements in pyrites: the reductive dissolution of iron/manganese oxyhydroxide aggregates fueled by the enhancement of AOM and substitution for ferrous in pyrites contribute to the enrichments of Mo, Co and Ni in pyrites. Elements with faster water exchange kinetics rates than Fe, such as Cu, Pb and Zn, rather precipitate as independent metal sulfides than incorporating into pyrite, thus resulting in the depletion of these trace elements in pyrites. This study provides novel insight into the deep-sea trace element cycle between sediments and authigenic pyrites, establishing geochemical indicators of AOM based on trace element patterns in pyrites.

Seasonal bioaccumulation and biomagnification of typical organochlorine pesticides in the Pearl River Estuary, South China - Xutong Zhang; Yiye Jiang; Yanhong Zeng; Jian Guo; Ling Long; Zijian Pan; Yankuan Tian; Yanting Zhang; Xiaojun Luo; Pingan Peng; Bixian Mai (Environmental Pollution, 2025)

Constraining sulfur and iron cycling in seep systems: insights from authigenic pyrite signatures - Qinyi Zhang; Daidai Wu; Yanting Ling; Xuan Chen; Shengyi Mao; Jie Liu; Guangrong Jin (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Mass concentrations, compositions and burial fluxes of nano- and micro-plastics in a multi-species saltmarsh - Yan Zhang; Yanting Wang; Peiyuan Zhu; Siyuan Jing; Jiana Li; Thomas Cherico Wanger; Weiping Liu; Kai Liu; Xiaogang Chen; Ling Li (Environmental Pollution, 2024)

Optimizing energy recovery from agroforestry waste: Char and inorganic influence on reactivity through co-gasification with coal - Shengli Shi; Xinsha Zhang; Yanting Wa; Weihui Zhou; Fayan Wang; Yueque He; Ling Xia (Process Safety and Environmental Protection, 2024)

The construction and immunogenicity analyses of a recombinant pseudorabies virus with Senecavirus A VP3 protein co-expression - Qian Tao; Lei Xu; Yang Zhang; Yanting Yang; Zheyan Liu; Tong Xu; Siyuan Lai; Yanru Ai; Ling Zhu; Zhiwen Xu (Veterinary Microbiology, 2024)

Application of amino acids nitrogen stable isotopic analysis in bioaccumulation studies of pollutants: A review - Yiye Jiang; Yanhong Zeng; Ruifeng Lu; Yanting Zhang; Ling Long; Xiaobo Zheng; Xiaojun Luo; Bixian Mai (Science of The Total Environment, 2023)

Vitamin D deficiency leads to the abnormal activation of the complement system - Huan Li; Xiaomin Xie; Guirong Bai; Dan Qiang; Li Zhang; Huili Liu; Yanting He; Yanpan Tang; Ling Li (Immunologic Research, 2023)
Vitamin D deficiency can damage the human immune system, and the complement system is a key component of the immune system. This study aimed to elucidate the mechanism by which vitamin D affects the immune system by analyzing the changes in the protein expression of the complement system under different vitamin D levels. We selected 40 participants and divided them into three groups according to their serum levels of 25-hydroxyvitamin D (25(OH)VD): group A, 25(OH)VD ≥ 40 ng/mL; group B, 30 ng/mL ≤ 25(OH)VD < 40 ng/mL; and group C, 25(OH)VD < 30 ng/mL. Serum samples were subjected to biochemical analysis, followed by proteomic analysis using high-throughput untargeted proteomic techniques. Vitamin D deficiency increased the levels of fasting blood sugar, fasting serum insulin, and homeostasis model assessment (HOMA) of insulin resistance and decreased the secretion of HOMA of β-cell function, which led to insulin resistance and glucose metabolism disorder. Moreover, vitamin D deficiency resulted in the abnormal expression of 56 differential proteins, among which the expression levels of complement factor B, complement component C9, inducible co-stimulator ligand, and peptidase inhibitor 16 significantly changed with the decrease in vitamin D content. Functional enrichment analysis of these differential proteins showed that they were mainly concentrated in functions and pathways related to insulin secretion and inflammation. In conclusion, vitamin D deficiency not only contributes to insulin resistance and glucose metabolism disorder but also causes abnormal protein expression, resulting in the abnormal activation of the complement system. This study provides a novel theoretical basis for further studies on the relationship between vitamin D and the immune system.

Mitochondrial fusion protein 2 regulates endoplasmic reticulum stress in preeclampsia - Dandan Sun; Hui Zhu; Ling Ai; Hanbing Wu; Yanting Wu; Jihua Jin (Journal of Zhejiang University-SCIENCE B, 2021)

RNA-Seq-based transcriptomic profiling of primary interstitial cells of Cajal in response to bovine viral diarrhea virus infection - Shengnan Li; Xinyan Hu; Ruixin Tian; Yanting Guo; Junzhen Chen; Zhen Li; Xinyan Zhao; Ling Kuang; Duoliang Ran; Hongqiong Zhao; Xiaohong Zhang; Jinquan Wang; et al. (Veterinary Research Communications, 2019)